Calorie Restriction and Extracellular ATP on Health and Longevity- A Perspective - Agraharam, Gopikrishna; Girigoswami, Agnishwar; Girigoswami, Koyeli (Current Nutrition & Food Science, 2023)
Oxidative stress is known to be generated within the organism by endogenous cellular mechanisms and can also be generated by external factors. Oxidative stress is known to be involved in various disease pathologies such as cancer, osteoarthritis, cardiovascular diseases, ageing, etc. The chronic/acute exposure to oxidative stress can easily damage cellular integrity through damaging the cellular DNA, mitochondrial DNA, proteins and other organelles that leads to malfunctioning of organs in the process of ageing. Mitochondrial respiration is one of the causes involved in the production of reactive oxygen species while generating bioenergetics (ATP) that provide energy to the cell for maintaining the cellular integrity through the electron transport chain mechanism, and on the other hand, it generates free-radicals that could cause damage to the cellular organelles and biomolecules. In relation to this context, longevity through the calorie restriction method could be due to the generation of lower reactive oxygen species and age-related diseases in vivo but accelerating loss of brain’s grey matter could be due to the depletion of energy. This is because intracellular ATP is the vital source of energy and extracellular ATP acts as signalling molecules. Using advanced technology such as nanotechnology for the internalization of extracellular ATP, and using it as an external source of energy could maintain cellular integrity and improve the healthy longevity status when combined with the calorie restriction method. In this perspective article, we have presented a brief overview and a hypothesis suggesting that the calorie restriction and extracellular ATP treatment could circumvent the mitochondrial pathway and alleviate oxidative stress, thereby improving health and enhancing longevity.
Keywords: longevity